2002
DOI: 10.1016/s0022-5347(05)64843-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow, Pressure and Compliance in the Male Human Bladder

Abstract: Human bladder blood flow tends to increase with increasing volume and pressure, and depends largely on local regulation. At capacity bladder blood flow is significantly decreased. Immediately after bladder drainage there is a rebound in blood flow, allowing reperfusion to occur. Decreased bladder blood flow and decreased bladder wall compliance correlated strongly, suggesting that ischemia may lead to structural changes in the bladder wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 29 publications
6
56
0
Order By: Relevance
“…Histological studies have shown fibrosis formation or denervation in the bladder samples from elderly male and female patients without BOO 104106 . These observations were supported by the study of Kershen et al (2002) which showed that decreased bladder blood flow and decreased bladder wall compliance correlated strongly, suggesting structural changes in the bladder wall induced by ischemia 107 . Moreover, pelvic arterial insufficiency such as caused by atherosclerosis, is also strongly associated with erectile dysfunction (ED) 108, 109 .…”
Section: Risk Factorssupporting
confidence: 63%
“…Histological studies have shown fibrosis formation or denervation in the bladder samples from elderly male and female patients without BOO 104106 . These observations were supported by the study of Kershen et al (2002) which showed that decreased bladder blood flow and decreased bladder wall compliance correlated strongly, suggesting structural changes in the bladder wall induced by ischemia 107 . Moreover, pelvic arterial insufficiency such as caused by atherosclerosis, is also strongly associated with erectile dysfunction (ED) 108, 109 .…”
Section: Risk Factorssupporting
confidence: 63%
“…First, the bladder wall is not merely a membrane that transfers pressure from the intra-abdominal space to the bladder content. Bladder wall compliance differs between patients and depends on several factors like age, BMI, filling status and bladder perfusion/ischemia [11]. Second, IAP reflects the relationship between the intra-abdominal volume and abdominal compliance.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, the significantly reduced detrusor blood flow in both full and empty bladder states was also demonstrated by Doppler ultrasonography in patients with BOO. 38 Contrary to these findings, previous publications reported either inconsistent variations in blood flow during BOO 39 or increased blood flow with increasing volume and pressure; 40 however, these studies were either experimental (not performed on human bladders) or reporting results from early and/or very mild phases of obstruction.…”
Section: Pathophysiology Of Lutsmentioning
confidence: 88%